Determining SARS-CoV-2 non-infectivity state–A brief overview - Brynjolfsson, Siggeir F.; Sigurgrimsdottir, Hildur; Gudlaugsson, Olafur; Kristjansson, Mar; Kristinsson, Karl G.; Ludviksson, Bjorn R. (Frontiers in Public Health, 2022)
From the beginning of the COVID-19 pandemic, it has claimed over 6 million lives, and globally the pandemic rages with detrimental consequences, with the emergence of new more infectious and possibly virulent variants. A clinical obstacle in this battle has been to determine when an infected individual has reached a non-infectious state. Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) can be transmitted under diverse circumstances, and various rules and regulations, along with different testing methods, have been applied in an attempt to confine the transmission. However, that has proven to be a difficult task. In this review, we take together recently published data on infectivity and transmission of SARS-CoV-2 and have combined it with the clinical experience that physicians in Iceland have accumulated from the pandemic. In addition, we suggest guidelines for determining when patients with COVID-19 reach a non-infectious state based on a combination of clinical experience, scientific data, and proficient use of available tests. This review has addressed some of the questions regarding contagiousness and immunity against SARS-CoV-2.